Non-unique fixed point results in extended b2-metric spaces - alkaleeli, sameehah; Elmabrok, Abdelhamid (Libyan Journal of Science &Technology, 2022)
In this paper,we present some non-unique fixed-point theorems for self-mapping in the setting of an extended b2-metric space. Our results generalize and widen some results of Alqahtani et al. (2018a).